Free radical scavenging and antifatigue activities of Saussurea involucrata polysaccharides - RL Zheng; GS Liu; GX Xing; ZJ Jia; M Du; LQ Tan (Acta Pharmacologica Sinica, 2017)
Free radical scavenging and antifatigue activities of Saussurea involucrata polysaccharides